Pengaruh Perception of Easy dan Perception Of Easefulness Terhadap Decision Usage FINA APP Pada PT. BCA Finance Medan - Setiyawan, Dedy; Rafiki, Ahmad; Wijaya, Muslim (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine the effect of Perception Of Ease and Perception Of Easefulness on Decision Usage FINA APP at PT BCA Finance Medan. This research was prepared using quantitative methods using quantitative methods. The sample of this study were 96 respondents who were users of the FINA App application and one of the customers at PT BCA Finance Medan using a sample collection technique, namely purposive sampling technique. Data collection is done by distributing questionnaires directly so that the data collected will be processed using SPSS to obtain research results. Based on the results of the study, it was found that partially Perception Of Ease has a positive and significant effect on Decision Usage, partially Perception Of Usefulness has a positive and significant effect on Decision Usage and simultaneously Perception Of Ease and Perception Of Usefulness simultaneously have a positive and significant effect on Decision Usage FINA APP at PT BCA Finance Medan. In addition, the coefficient of determination in the Adjusted R Square column is 0.682 (68.2%), which describes that the value of variance owned by Decision Usage from the Perception Of Ease and Perception Of Usefulness variables is 68.2% and the remaining 31.8% is influenced by other variables or factors not examined and not explained in this study.